Repeated Measures of Placental Growth Factor, Placental Protein 13, and A Disintegrin and Metalloprotease 12 at First and Second Trimesters for Preeclampsia Screening - Boucoiran, Isabelle; Suarthana, Eva; Rey, Evelyne; Delvin, Edgard; Fraser, William B.; Audibert, François (American Journal of Perinatology, 2013)
Objective To determine the utility of cross-trimester repeated measures of placental protein 13 (PP13), A disintegrin and metalloprotease 12 (ADAM12), and placental growth factor (PlGF) for preeclampsia (PE) screening.Study Design A prospective cohort study of 893 nulliparous women who had serum sampling at 11 to 14 and 18 to 22 weeks. Biomarker levels were adjusted on maternal characteristics and gestational age. The accuracy and validity of maternal characteristics with single and repeated markers to predict PE were evaluated.Results First-trimester PlGF was the best biomarker for PE (mean: 0.85 multiples of the expected median [MoM]) and early onset PE (0.79 MoM). First-trimester screening performances were not significantly improved by second-trimester markers. Area under the receiver operating characteristic curve was 0.73 (95% confidence interval [CI] 0.65 to 0.81) with first-trimester PlGF and 0.71 (95% CI 0.63 to 0.80) with first- and second-trimester PlGF (p = 0.301).Conclusion Repeated measures of PlGF, ADAM12, and PP13 at second trimester did not improve PE screening compared with first-trimester measures.
Keywords: preeclampsia; screening; PlGF; PP13; ADAM12